Customizing Hotel Services by Mobile Application (CHSMA) - Ammourah, Boraq Ahmad (2009)
Hotel Services are commonly provided by hotels in order to satisfy customer’s needs where it usually done by manual or website. Developing systematic ways to improve the hotel services where to relate with the Mobile Application system to the customizing of the hotel service where provide an access to the hotel information and also to help customer to making decision. The ultimate goal is the ability to help customer to customizing hotel services by mobile application to arrive at a better overall system. The purpose of this proposal is to take a small step in the direction of developing a unifying approach for reasoning about customizing hotel services by mobile application, however propose to design mobile application for hotel reservation as 85% of Malaysian own hand phone, so in this study a design the application and prototype will be developed using mobile device to help the reservation process in anytime,anywhere, quickly and easily.